2020
DOI: 10.1103/physrevd.102.034027
|View full text |Cite
|
Sign up to set email alerts
|

QCD phase structure from functional methods

Abstract: We discuss the QCD phase structure at finite temperature and chemical potential for 2-flavor and 2 þ 1flavor QCD. The results are achieved by computing QCD correlation functions within a generalized functional approach that combines Dyson-Schwinger equations (DSE) and the functional renormalization group (fRG). In this setup fRG precision data from [A. K. Cyrol, M. Mitter, J. M. Pawlowski, and N. Strodthoff, Phys. Rev. D 97, 054006 (2018).] for the vacuum quark-gluon vertex and gluon propagator of 2-flavor QCD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
140
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 88 publications
18
140
0
Order By: Relevance
“…The normalization is given by the maximum of the susceptibility at the physical pion mass; see Eq. (5). We observe that the results from the two methods agree very well for m π ≳ 30 MeV.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The normalization is given by the maximum of the susceptibility at the physical pion mass; see Eq. (5). We observe that the results from the two methods agree very well for m π ≳ 30 MeV.…”
Section: Resultsmentioning
confidence: 56%
“…Fitting the relation 7 M is the maximum of the susceptibility at the physical pion mass; see Eq. (5). The lattice QCD data have been taken from Refs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous lattice attempts to overcome the sign problem provide reliable information only in the region of small baryon density [2]. In the absence of straightforward results from lattice simulation of QCD, one applies different analytical approaches to study the ðμ; TÞ phase diagram: mean field approaches [3][4][5][6][7][8][9], the method of Dyson-Schwinger equations and the renormalization group [10][11][12][13], the large-N c approach [14], perturbative QCD [15,16] and others. Although the results obtained theoretically are important, it is rather difficult to estimate the reliability of these predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The studies have suggested that the QCD matter experiences a crossover at zero chemical potential as the temperature increases. At low temperature, the QCD matter could be well described by the hadron resonance gas, while it gradually becomes quark gluon plasma at high temperature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. As the temperature changes, the thermal mass of hadrons will shift, the thermal a e-mail: gao@thphys.uni-heidelberg.de (corresponding author) b e-mail: mding.ectstar@gmail.com width will usually get larger and the decay of hadrons will then change.…”
Section: Introductionmentioning
confidence: 99%